Glass Formation and Properties of Multicomponent Glasses of the As2Se3-Ag2Te-GeTe System - Ina Karadashka; Vladislava Ivanova; Valeri Jordanov; Veronika Karadjova (Inorganics, 2023)
Chalcogenide alloys of As2Se3-Ag2Te-GeTe were synthesized using the melt-quenching technique. By the visual and XRD analyses, the state of obtaining alloys was proven (glass, crystalline, glass + crystalline), and the glass formation region in the system was established. The thermal characteristics of some samples were determined—temperatures of glass transition (Tg); crystallization (Tcr); and melting (Tm). The basic physicochemical parameters, such as density (d) and Vickers microhardness (HV), were measured. Compactness (C), as well as some thermomechanical characteristics, such as module of elasticity (E), volume (Vh), and formation energy (Eh) of micro-voids, were calculated, and the influence of the composition on these characteristics was investigated. The addition of silver telluride resulted in a decrease in Tg and HV values and an increase in d and Vh values. No thermochemical effects of crystallization or melting were detected in some of the alloys. The obtained results were in agreement with the available literature data for similar systems.